Analysis of Dielectric Properties of Lithium Phosphate Glasses - Hockicko, Peter; Bury, Peter; Munoz, Francisco (Communications - Scientific letters of the University of Zilina, 2013)
Dielectric relaxation spectra of lithium phosphate glasses are used to analyze the change of real and imaginary part of complex permittivity including loss tangent of ion conductive glasses. The experimental results getting from a.c. and d.c. electric measurements on Li phosphate glasses are analyzed, discussed and compared. Frequency dependence of the permittivity spectra is found to be consistent with the analysis of d.c. electrical conductivity. The universal a.c. conductivity law (universal dynamic response) for glass ionic conductor was confirmed. Arrhenius graphs constructed from a.c. and d.c. electrical measurements including loss tangent are used to characterize the relaxation processes and transport mechanisms connected with the mobility of conductive ions.